2017
DOI: 10.1101/215921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuous high-resolutionin vivoimaging reveals tumor-specific dissemination in an embryonic zebrafish xenograft model

Abstract: Mechanisms mediating tumor metastasis are crucial for diagnostic and therapeutic targeting. Here, we take advantage of a transparent embryonic zebrafish xenograft model (eZXM) to visualize and track injected human leukemic and breast cancer cells in real time using selective plane illumination microscopy (SPIM) for up to 30 hours. Injected cells exhibited disease-specific patterns of intravascular distribution with leukemic cells moving faster than breast cancer cells. While breast cancer cells predominantly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 53 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…In our previous study, we utilized high resolution selective plane illumination microscopy (SPIM) to characterize in detail, the dissemination behavior of injected human breast cancer cells in vivo. 23 Also, SPIM imaging allowed us to monitor the cells in real time with high spatial and temporal resolution, thereby analyzing the cancer cell behavior, migration pattern, extravasation and invasion of tumor cells into the zebrafish embryos. Also 80% of the injected cells retained inside the larvae until 3 dpi, provided sufficient window for the drug screening.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, we utilized high resolution selective plane illumination microscopy (SPIM) to characterize in detail, the dissemination behavior of injected human breast cancer cells in vivo. 23 Also, SPIM imaging allowed us to monitor the cells in real time with high spatial and temporal resolution, thereby analyzing the cancer cell behavior, migration pattern, extravasation and invasion of tumor cells into the zebrafish embryos. Also 80% of the injected cells retained inside the larvae until 3 dpi, provided sufficient window for the drug screening.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have validated the model for anti-leukemic drug and other studies have shown a pre-treatment drug sensitivity platform for patientderived multiple myeloma and breast tumor cells in zebrafish xenografts. 23,30,48,49 In the current study, we have utilized the previously characterized breast metastatic zebrafish embryonic xenografts for testing the efficacy of PtPP-loaded HA nanoparticles as local drug carriers. Previous studies described that zebrafish embryos can be employed to test the toxic effects of HA nanoparticles with different shapes, albeit in an indirect manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples include patient-derived samples, xenotransplantation samples, observations of induced cancer cells or small-scale screens of selected compounds. Our multi-sample platform has already been applied successfully to such a study where the influence of the Rho-kinase inhibitor fasudil was investigated on drug-treated and non-drug-treated fish in the same experiment (Asokan et al, 2017preprint). In future, the platform will provide the required sample capacity to tackle more such projects.…”
Section: Discussionmentioning
confidence: 99%